2019
DOI: 10.7454/jki.v0i0.873
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Kemampuan Kepala Keluarga Dalam Memenuhi Kebutuhan Ekonomi Keluarga: Studi Fenomenologi Pengalaman Orang Dengan Gangguan Jiwa Paska Pasung

Abstract: Decreasing the Capabilities of the Breadwinner in Meeting the Economic Needs of Families: A phenomenology Study of the Mental Illness People Post-Pasung. The breadwinner of the family economically responsible for meeting the needs of all family members, including clothing, food, and housing needs. A breadwinner of the family with mental illness after pasung needs to adjust to social functions including the ability to work and be involved in social relations. Pasung is physical restraint and confinement by fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the neighbors and the environment were fully supportive for the breadwinner to continue working by giving support for casual work like domestic chores. This support increased their confidence and was a strong basis for them to continue their role as head of the family 7 Daulima (2018) [31] The validity and reliability results showed that the content of this instrument is valid once improvements had been made to the statement item numbers 16 and 17. It was also shown to be reliable by the consistency of the responses with an alpha value of .729.…”
Section: Case Control Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the neighbors and the environment were fully supportive for the breadwinner to continue working by giving support for casual work like domestic chores. This support increased their confidence and was a strong basis for them to continue their role as head of the family 7 Daulima (2018) [31] The validity and reliability results showed that the content of this instrument is valid once improvements had been made to the statement item numbers 16 and 17. It was also shown to be reliable by the consistency of the responses with an alpha value of .729.…”
Section: Case Control Studiesmentioning
confidence: 99%
“…Helena, Daulima and Wardani [37] also identified that the family experienced a psychosocial change after their family member was placed in pasung, mainly if the person had previously been the head of the household or primary breadwinner. In these circumstances, other family members now had to find new ways of gaining income for the family or taking on the role as head of household [29,31]. Consequently, many families with a PWMD lived in poverty.…”
Section: Interpersonal Relationshipsmentioning
confidence: 99%
“…Rumah sakit jiwa (RSJ) memegang peran penting dalam pembangunan kesehatan jiwa di Indonesia terutama dalam mengembalikan keberfungsional sosial para penyandang penyakit jiwa (Ekasari & Augus, 2020). Rumah sakit jiwa memiliki fungsi sosial paling tinggi dibandingkan dengan jenis rumah sakit yang lain karena pasien yang ditangani umumnya merupakan pasien yang memiliki kemampuan ekonomi yang rendah, karena secara psikis para penyandang gangguan jiwa tidak memungkinkan memperoleh penghasilan sendiri dan menjadi beban sosial bagi keluarga dan masyarakat (Daulima et al, 2019;E. Puspitasari, 2017).…”
Section: Pendahuluanunclassified
“…Detention in PSMD occurs because of fear of the risk of violent behavior. 18 Violent behavior by PSMD is when the patient has a history that can endanger himself, others, or the environment physically or emotionally. 19 Violent behavior in the community and health services carried out by patients against others or otherwise torturing oneself.…”
Section: Subject Characteristicsmentioning
confidence: 99%